Monitoring of lubrication and wear in-situ by triboelectrification under grease lubrication - Yiming Lei; Yange Feng; Zixiang Wu; Qiang Gao; Zhuopei Zhang; Wenpeng Wang; Liucheng Wang; Youqiang Wang; Daoai Wang (Friction)
The stable operation of friction pairs is one of the most critical factors to maintain the stable operation of mechanical equipment. The real-time monitoring of lubrication state of the friction pair is very important to ensure the normal operation of machinery and realize early warning of wear failure, but it is also a big challenge. In this article, a new lubrication in-situ monitoring system is designed, which can monitor the lubrication and wear state of friction pairs through triboelectrification. The current acquisition module and friction coefficient acquisition module are integrated into a high vacuum hydrodynamic oil film thickness measuring instrument to explore the intrinsic relationship between triboelectricity and friction coefficient curves. When severe wear occurs, the oil film at the interface of the friction pair is no longer complete, and the accumulated triboelectric charge at the interface of the friction pair breaks down the air and causes discharge, the friction current suddenly increases from nanoampere level to microampere level. The time node when discharge occurs at the steel ball interface is well consistent with the time node when the friction pair suffers serious wear. According to the corresponding relationship between the triboelectric current and the friction and wear status of the friction pair, an early wear warning monitoring system is designed to monitor the operating status of the friction pair in real time through triboelectric signals. When the mechanical friction pair is worn, the early warning system will send out sound and light alarm signals and send real-time warnings to the mobile terminal through the Internet of Things, providing a new and reliable method for real-time monitoring of friction and wear of grease-lubricated machinery.